A review of the factors that influence pesticide residues in pollen and nectar: Future research requirements for optimising the estimation of pollinator exposure. (June 2019) - Gierer, Fiona; Vaughan, Sarah; Slater, Mark; Thompson, Helen M.; Elmore, J. Stephen; Girling, Robbie D.
Abstract: In recent years, the impact of Plant Protection Products (PPPs) on insect pollinator decline has stimulated significant amounts of research, as well as political and public interest. PPP residues have been found in various bee-related matrices, resulting in governmental bodies worldwide releasing guidance documents on methods for the assessment of the overall risk of PPPs to different bee species. An essential part of these risk assessments are PPP residues found in pollen and nectar, as they represent a key route of exposure. However, PPP residue values in these matrices exhibit large variations and are not available for many PPPs and crop species combinations, which results in inaccurate estimations and uncertainties in risk evaluation. Additionally, residue studies on pollen and nectar are expensive and practically challenging. An extrapolation between different cropping scenarios and PPPs is not yet justified, as the behaviour of PPPs in pollen and nectar is poorly understood. Therefore, this review aims to contribute to a better knowledge and understanding of the fate of PPP residues in pollen and nectar and to outline knowledge gaps and future research needs. The literature suggests that four primary factors, the crop type, the application method, the physicochemical properties of a compound and the environmental conditions have the greatest influence on PPP residues in pollen and nectar. However, these factors consist of many sub-factors and initial effects may be disguised by different sampling methodologies, impeding their exact characterisation. Moreover, knowledge about these factors is ambiguous and restricted to a few compounds and plant species. We propose that future research should concentrate on identifying relationships and common features amongst various PPP applications and crops, as well as an overall quantification of the described parameters; in order to enable a reliable estimation of PPP residues in pollen, nectar and other bee matrices. Graphical abstract: Image 1 Highlights: Only fragmentary datasets of pesticide residue values in pollen and nectar exist. Poor knowledge on fate and relationship amongst different pesticides in bee products. Extrapolation between different pesticide applications on residues is not possible. Manifold parameters influence the pesticide residues in bee products. Significant need for detailed research on pesticide residues in pollen and nectar. Abstract : Pesticide residue values within pollen and nectar have potentially significant consequences for the reliability of risk assessments for wild and managed bee populations, however, the reasons and mechanisms underlying variations in residues are poorly understood and require greater investigation.